GreenLoops: Revolutionizing sorghum biomass into clean energy via a smart agro-industrial ecosystem - Hesti Indriani; Ikhsan Muttaqin; Bintang Yolanda S. Simanjuntak; Taufik (Social Agriculture, Food System, and Environmental Sustainability, 2025)
Background: Indonesia’s agricultural sector generates more than 150 million tons of biomass waste annually, making up nearly 60% of the country’s organic waste and many farmers burn it openly. Although inexpensive, this practice accelerates greenhouse gas emissions and worsens environmental degradation. This research aims to develop an integrated technological approach for agro-industrial waste management that minimizes emissions, creates economic value, and promotes circular economy principles in support of Indonesia’s net-zero emission target. Methods: This study employs a mixed-method approach by integrating Internet of Things (IoT), Artificial Intelligence (AI), and Augmented Reality (AR) technologies. The system consists of Sorcast, an intelligent forecasting tool using Random Forest and LSTM models to predict sorghum yield and biomass composition; Smartbriq, an AR-based application that provides step-by-step guidance for producing biomass briquettes; and E-Cowaste, a digital marketplace that facilitates traceable biomass waste transactions with features such as carbon calculators, smart contracts, and certification mechanisms. Findings: Results show that the integrated system, referred to as SWTS, enhances resource efficiency and significantly reduces greenhouse gas emissions by enabling predictive analytics and real-time monitoring. Smartbriq increases farmer engagement by simplifying briquette production, while E-Cowaste improves transparency and accountability in biomass trading. Conclusion: The findings suggest that integrated digital systems provide an effective alternative to reducing agricultural waste, mobilize farmers toward sustainable practices, and generate both economic and environmental benefits. Novelty/Originality of this article: The novelty lies in combining AI-based forecasting, AR-assisted briquette production, and blockchain-enabled waste trading into a unified, scalable model for transforming agricultural waste sustainably in Indonesia.